Effect of diets of different level of protein on the recovery of kwashiorkor children. - A. Jalil, A. Khan; Khattak, Muhammad Muzaffar Ali Khan (Northeast Regional Environmental Public Health Center, 2005)
The effect of diets of different levels of protein on the recovery of Kwashiorkor and marasmic Kwashiorkor children was studied for 3 weeks in Pakistan. Sixty Kwashiorkor children of less than 5 years age were grouped into 4, each group was having 15 children. For each group, two diets, one for early recovery and the other for catch up growth, were prepared from fresh buffalo milk, banana, soybean oil and glucose. The basal (reference) and test diets for early recovery and catch up growth had constant calories and variable amounts of protein. The basal diets and test diets were assigned to group 1, 2, 3 and 4 respectively. The early recovery diets were fed for the 5 days and the catch up growth diets were fed for the remaining duration. The early recovery of the children was measured in terms of weight gain and weight was taken weekly. The combined average intake/day of the early recovery and catch up growth diets were calculated. The average caloric intake of group 1, 2, 3 and 4 were 140 ± 19, 133 ± 22, 133 ± 16 and 153 ± 8 Kcal/Kg body weight/day respectively. The average protein intake of groups 1, 2, 3 and 4 were 2.7 ± 0.4, 2.9 ± 0.4, 3.2 ± 0.4 and 3.6 ± 0.2 g/Kg body weight/day respectively. The groups of test diets gained more weight than the group of basal diet, however, the results were not significant at P<0.05. the data revealed that the diet that provided 133 ± 22 Kcal/Kg body weight/day and 2.9 ± 0.4 g protein/ kg body weight/day was better for the 2.9 ± 0.4 g protein/ kg body weight/day better for the recovery of Kwashiorkor and marasmic Kwashiorkor children